Diabetic ketoacidosis and thyroid storm: coexistence of a double trouble. (27th September 2018) - Rajput, Rajesh; Jain, Deepak; Pathak, Vaibhav; Dangi, Anoop
Abstract : Diabetic ketoacidosis (DKA) and thyrotoxic crisis are both endocrine emergencies. Here, we present a case of a patient who presented with DKA and on further evaluation was found to also have a thyrotoxic crisis. The coexistence of both of these endocrine emergencies simultaneously is extremely rare and heralds grave prognosis unless identified and treated promptly.